The reproduction of regional inequalities through social capital - Mueller, Airton Adelar (Revista Espaço Acadêmico, 2019)
The vast extent of the social capital bibliography points out its collective and individual dimensions. In this regard, stands out the collective level for the study of regional development dynamics. This paper discusses and attempts to outline that: a) not only the collective social capital concept but also the individual social capital have heuristic value for regional development studies and b) both levels (individual and collective) can contribute to the reproduction of existing regional inequalities, or even to amplify them. The first section of this paper will examine the interconnections between social networks, individual social capital, migratory movements and regional inequalities. These interconnections are supported by data on migration and profile of migrants of Meso-regions of the Rio Grande do Sul state in Brazil. Secondly, this paper will argue that the collective aspect of social capital can increase the reproduction of regional inequalities already existent. In this regard, it is discussed that the logic of reproduction of social inequalities presented by Pierre Bourdieu can also be valid to understand the effects of collective social capital in the different dynamics of regional development. This argument is illustrated by data about the distribution of the world`s wealth and population according to selected regions and countries.